2003
DOI: 10.1523/jneurosci.23-08-03423.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Processing in Spoken Language Comprehension

Abstract: Understanding spoken language requires a complex series of processing stages to translate speech sounds into meaning. In this study, we use functional magnetic resonance imaging to explore the brain regions that are involved in spoken language comprehension, fractionating this system into sound-based and more abstract higher-level processes. We distorted English sentences in three acoustically different ways, applying each distortion to varying degrees to produce a range of intelligibility (quantified as the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

122
612
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 661 publications
(741 citation statements)
references
References 52 publications
(63 reference statements)
122
612
7
Order By: Relevance
“…Compared to noise alone, speech in noise and speech in quiet together evoked statistically significant activity in the STG bilaterally and in the left MTG (see Figure 5a). This has been observed in other studies as well (e.g., Binder et al, 2004;Davis & Johnsrude, 2003;Obleser et al, 2007;Zekveld et al, 2006). Figure 5a.…”
Section: Fmri Resultssupporting
confidence: 88%
“…Compared to noise alone, speech in noise and speech in quiet together evoked statistically significant activity in the STG bilaterally and in the left MTG (see Figure 5a). This has been observed in other studies as well (e.g., Binder et al, 2004;Davis & Johnsrude, 2003;Obleser et al, 2007;Zekveld et al, 2006). Figure 5a.…”
Section: Fmri Resultssupporting
confidence: 88%
“…The Hickok and Poeppel study showed that when the task load is high, requiring both speech identification and speech categorization, the activated frontal region extends to the premotor cortex [17] . Also, when speech signals are distorted, the motor cortex is markedly activated [45,46] . Interestingly, non-verbal signals can activate motor areas [31,47] , and there is no difference in activation magnitude in the motor cortex between perceiving speech and perceiving nonverbal sounds [31] .…”
Section: Anatomical and Functional Associations Between The Auditorymentioning
confidence: 99%
“…Interestingly, non-verbal signals can activate motor areas [31,47] , and there is no difference in activation magnitude in the motor cortex between perceiving speech and perceiving nonverbal sounds [31] . Some studies have further shown that blurred speech causes even stronger activation in the bilateral premotor cortex, compared to clear speech [45] and perceiving a foreign language causes larger activation in the motor cortex than the native language [25] . Also, lowfrequency words induce higher activation in the motor cortex than high-frequency words [48] .…”
Section: Anatomical and Functional Associations Between The Auditorymentioning
confidence: 99%
“…Converging evidence from several methodologies, such as ERP (Aydelott, Dick, & Mills, 2002), fMRI (Davis & Johnsrude, 2002;Poldrack et al, 2001), and neuropsychology (Aydelott Utman, Blumstein, & Sullivan, 2001;Moineau, Dronkers, Ludy, & Bates, 2002) suggest that the brain regions and processes affected by such degradations overlap to a large extent with those affected in biologically based language breakdown.…”
Section: Introductionmentioning
confidence: 99%